2020
DOI: 10.1126/sciadv.aaz3154
|View full text |Cite
|
Sign up to set email alerts
|

The NALCN channel complex is voltage sensitive and directly modulated by extracellular calcium

Abstract: The sodium leak channel (NALCN) is essential for survival in mammals: NALCN mutations are life-threatening in humans and knockout is lethal in mice. However, the basic functional and pharmacological properties of NALCN have remained elusive. Here, we found that robust function of NALCN in heterologous systems requires co-expression of UNC79, UNC80, and FAM155A. The resulting NALCN channel complex is constitutively active and conducts monovalent cations but is blocked by physiological concentrations of extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
97
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 41 publications
16
97
3
Order By: Relevance
“…1e). These ndings are distinct from other recent studies 40,41 . Moreover, we observed no inactivation of the steady state current by setting the prepulse potential to different levels when NALCN channel was co-expressed with auxiliary subunits ( Supplementary Fig.…”
Section: Speci C Interactions Between Nalcn and Fam155acontrasting
confidence: 99%
See 4 more Smart Citations
“…1e). These ndings are distinct from other recent studies 40,41 . Moreover, we observed no inactivation of the steady state current by setting the prepulse potential to different levels when NALCN channel was co-expressed with auxiliary subunits ( Supplementary Fig.…”
Section: Speci C Interactions Between Nalcn and Fam155acontrasting
confidence: 99%
“…These observations indicate that the auxiliary subunits are essential for a functional NALCN ( Supplementary Fig. 1a), consistent with previous studies 30,31 . The electrophysiological properties of NALCN suggested that it tends to maintain the RMP in a manner reminiscent the Le Chatelier's principle in chemical equilibria.…”
Section: Functional Characterization Of Nalcn By Electrophysiologysupporting
confidence: 92%
See 3 more Smart Citations